Rapid isoelectric focusing of plasmid-mediated beta-lactamases with Pharmacia PhastSystem. - Huovinen, S (1988)
A modified isoelectric focusing method for rapid semiquantitative identification of plasmid-mediated beta-lactamases by use of the Pharmacia PhastSystem (Uppsala, Sweden) is described. Sonication of bacterial colonies collected directly from growth plates decreased the time required for the procedure. With sonic extracts of known beta-lactamase-producing strains used as controls, the assay could be completed in less than 2 h.